Pridelek in kakovost hmelja v Sloveniji v prvem četrtletju tega stoletja - Trošt, Žan (Hmeljarski bilten, 2025)
At the beginning of the 21st century, around 1,800 ha of hops were planted in Slovenia, with more than 200 hop growers producing hops, and the size of hop acreage on hop farm was around 9 ha. The Aurora variety dominated, planted in almost two-thirds of all hop fields. In 2012, less than 1,200 ha were planted with hops, but the areas started to grow again soon and are now around 1,600 ha. There have been around 120 active hop growers in recent years, and the size of the hop farm is increased at 14 ha. Over the years, the areas planted with Aurora have decreased, while the Celeia variety has become increasingly popular. The areas planted with the Bobek variety have been stable in the last 25 years, while the share of the Savinjski golding area is slowly but steadily decreasing. A similar picture applies to the yield of these varieties. Based on the review of weather conditions in the growing years, we can conclude that dry and hot conditions negatively affect both the yield and the quality of hops (alpha acids). The lowest alpha acid contents were achieved in the extremely hot and dry years of 2003 and 2013. The alpha acid contents of the Aurora variety have been increasing slightly in the last 25 years, while some other varieties are less able to adapt to weather changes. This is most noticeable in the old variety Savinjski golding, which has not reached the minimum reference values for alpha acid content in recent years. The quality of hops is also largely related to drying, the more dried the hops are, the more hop waste they contain, so drying has a major impact on the final quality of the crop. The content of leaves and stalks in hops has decreased for half over the last 25 years, thanks to the modernization of harvesting machines.
Keywords: alpha-acids; hmelj; hmeljarstvo; hop growing; hop quality; hop yield; hops; kakovost hmelja; pridelek hmelja; vsebnost alfa-kislin